Memory for emotional information and alexithymia A systematic review - Apgáua,Leonardo T. (2019)
ABSTRACT. Alexithymia is a deficit in the recognition, expression and regulation of emotions, which has the following features: difficulty in identifying or describing feelings, difficulty distinguishing between feelings and bodily sensations, stringent imaginal processes, and externally oriented cognitive style. This personality trait is associated with many psychiatric and psychosomatic disorders, as well as with risky behaviors. Objective: To investigate whether this trait is also associated with reduced memory for emotional information. Methods: A review of articles investigating the possible damage caused by alexithymia to implicit and explicit memory for emotional information was conducted. Results: Although the studies concerning implicit memory presented divergent results, most studies on explicit memory suggested a deficit for emotional information retention in high-alexithymia individuals. Conclusion: The reviewed data support the notion that the typical increase in episodic memory for emotional information is reduced in high-alexithymia individuals.